Answer:
Step-by-step explanation:
Given the function
[tex]f\left(x\right)\:=\:3x-1[/tex]
Finding the value of 'a':
Plugging x = -5 in order to find the value of 'a'
[tex]f\left(x\right)\:=\:3x-1[/tex]
[tex]f\left(-5\right)\:=\:3\left(-5\right)-1[/tex]
[tex]\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a[/tex]
[tex]=-3\cdot \:5-1[/tex]
[tex]\mathrm{Multiply\:the\:numbers:}\:3\cdot \:5=15[/tex]
[tex]=-15-1[/tex]
[tex]=-16[/tex]
Therefore,
Finding the value of 'b':
Plugging x = 4 in order to find the value of 'b'
[tex]f\left(x\right)\:=\:3x-1[/tex]
[tex]f\left(4\right)\:=\:3\left(4\right)-1[/tex]
[tex]\mathrm{Remove\:parentheses}:\quad \left(a\right)=a[/tex]
[tex]=3\cdot \:4-1[/tex]
[tex]=12-1[/tex] ∵ [tex]3\cdot \:4=12[/tex]
= 11
Therefore,
Finding the value of 'c':
Plugging x = 8 in order to find the value of 'c'
[tex]f\left(x\right)\:=\:3x-1[/tex]
[tex]f\left(8\right)\:=\:3\left(8\right)-1[/tex]
[tex]=24-1[/tex] ∵ [tex]3\cdot \:8=24[/tex]
= 23
Therefore,